Strength Analysis of LCT Lady Primus 39.5 m Ramp Door Structure Due to Changes in Tilt Angle Variations and Load Variations - Hartono Yudo; Kiryanto Kiryanto; Alji Fadilla Adha; Riyanto Wibowo (Institut Teknologi Sepuluh Nopember, 2023)
Of the several cases of accidents, the fall of a vehicle from a ship during loading and unloading occurred due to a break in the clevis ramp door. This study focused on the construction of the ramp door of the ship LCT Lady Primus 39.5 m. The purpose of this study is to determine the voltage characteristics that occur in ramp door construction, determine the location of the most critical components in ramp door construction, and determine the safety factor value in ramp door construction under each loading condition. This research uses the finite element method (FEM) and refers to the Indonesian Classification Bureau (BKI) rules. The vehicle loads used in this study were the Uro Vamtac, Panser Anoa, APC Komodo, and BMP 3F Tanks. The variations given are in the form of angular conditions of +108, 08, and -108. Validation was carried out on the model by comparing the results of simulation calculations with analytical calculations, and an error value of 2.8% was obtained. The material used is KI-A36, with a yield voltage of 235 Mpa. The results of the FEM analysis (finite element method) obtained a maximum stress of 82.31 Mpa located on a stiffener length 3 precisely at node 1249. The most considerable strain of 1.929 mm is located on the top plate at node 20495. The research results on cargo variations and tilt angles of the LCT Lady primus 39.5 m ship ramp door have met the criteria of the Indonesian Classification Bureau (BKI) rules.